Placing the operator at the centre of Industry 4.0 design: Modelling and assessing human activities within cyber-physical systems. (January 2020) - Fantini, Paola; Pinzone, Marta; Taisch, Marco
Highlights: Methodology for work design & assessment in CPS, industrial cases application. Multiple perspective emphasizing activities' features non replaceable by technology. Coverage of ordinary and irregular scenarios, such as failure and maintenance. General guidelines for CPS-enabled services to support human activities. A first step towards formal quantitative methods and simulations. Abstract: The Industry 4.0 vision, grounded on the integration of key technologies and Cyber-Physical-Systems (CPSs), is expected to profoundly modify the manufacturing sector. There is large consensus on the fact that work will change and different skills will be needed. However, whether the organization of work will evolve towards higher responsibility and decision-making of the employees or towards higher technological control is still an open question. The challenge is how to govern this evolution and purposely guide the process of integrating people within CPSs in order to move towards the desired scenario. This paper addresses this challenge, by proposing a methodology to support the design and assessment of different work configurations, jointly considering the uniqueness of human labour and the characteristics of cyber-physical production within a comprehensive framework. The method covers ordinary production as well as irregular scenarios, such as failure detection or maintenance intervention, particularly interesting for human work. The applicability of the method is illustrated through two industrial cases, leading to suggestions for training the personnel and for enhancing the whole cyber- physical-social system. Results include human-centric Key Performance indicators (KPIs) and general guidelines for work design. The approach encourages managers and engineers to clarify their strategy for human resources; develops a multi-perspective awareness on the role of workers; fosters an early detection of possible misalignment between the high-level strategies and the technical interventions on the shop floor. The modelling, analysis and assessment technique developed aims at representing a first step towards formal and quantitative methods to support the design of human work integrated within cyber-physical-systems.